Evektivitas Program Bimbingan Karir Berbasis Minat dan Bakat terhadap Perencanaan Masa Depan Siswa di SMP Negri 4 Kediri Tabanan - Mita Ayu Saputri; Kusuma Wardani; Putu Agus Semara Putra Giri (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
Students with effective career planning typically exhibit qualities including (1) comprehension of the professional landscape, (2) specific interests and aptitudes pertaining to a certain vocation, and (3) personality traits and values aligned with their career aspirations. Career advice services offer support to students by assisting in planning, problem-solving linked to occupations, and enhancing awareness of job roles. The introduction of community service activities yielded a result indicating that career guidance and counseling services enhance the ability to effectively execute career planning in alignment with students' talents and interests. This study seeks to evaluate the efficacy of a career advising program centered on interests and talents in enhancing students' future planning skills at SMP Negeri 4 Kediri. A multitude of junior high school pupils experience confusion in planning their futures due to a lack of understanding of their hobbies and talents. This program is intended to offer structured advice services that assist students in identifying their potential and formulating more pragmatic future plans. The research methodology employs a quasi-experimental design using a one-group pretest-posttest framework. The study's subjects comprised 30 grade IX pupils recruited purposively. The tool employed was a future planning questionnaire designed on the basis of career planning indicators. The data analysis results indicated a substantial rise in students' future planning scores following their participation in the program. Consequently, this curriculum has demonstrated efficacy in assisting students in preparing for the future in alignment with their interests and abilities